Pengaruh Sosial Media Marketing, Indluencer Dan Brand Image Terhadap Keputusan Customer Dalam Memilih Jasa MUA Ratih Devi Salon Di Denpasar - Amelia Paramitha Dewi, Ni Kadek Vira; Wirati Adriati, I Gusti Ayu (Economic Reviews Journal, 2025)
The rapid development of social media has changed the pattern of service marketing, especially in the beauty industry such as Make-Up Artist (MUA). Social media not only functions as a promotional tool, but also as a medium for building brand image and spreading influence through influencers. This study aims to analyze the influence of Social Media Marketing, Influencers, and Brand Image on Customer Decisions in choosing MUA services at Ratih Devi Salon in Denpasar, both partially and simultaneously. This study uses a quantitative approach with a survey method. The population in this study are customers who have used MUA services at Ratih Devi Salon in Denpasar, with samples determined using a purposive sampling technique. Data were collected through questionnaires distributed to respondents and analyzed using multiple linear regression analysis. Data testing included validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination (R²). The results showed that Social Media Marketing, Influencers, and Brand Image had a positive and significant influence on Customer Decisions in choosing MUA services at Ratih Devi Salon in Denpasar. Simultaneously, the three independent variables were also proven to have a significant influence on customer decisions. These findings indicate that effective digital marketing strategies, the right influencer support, and a strong brand image can increase trust and encourage consumer decisions in choosing MUA services.